The Twelve Years' Truce (1609) : peace, truce, war, and law in the Low Countries at the turn of the 17th century - Lesaffer, Randall (Legal history library, 2014)
The Twelve Years Truce covers the legal history of a crucial text in the formation of the Republic of the Northern Netherlands as a sovereign power and highlights its significance in the formation of the early modern laws of war and peace.